Workshop Pengelolaan Open Journal System (OJS) di Lingkungan Perguruan Tinggi Swasta Yayasan Pendidikan Persada Bunda Pekanbaru - Ahmad Saudi; Andi Kardian Riva’i; A’ang Chaarnaillan; Hanifahturahmi; Muhammad Fikri Vernanda (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
To facilitate the scientific work of students and lecturers, every tertiary institution is required to have a scientific journal based on the Open Journal System. Persada Bunda Pekanbaru College, whose scientific publications were previously in the form of journals, have not been managed electronically (have not used the Open Journal System) and need to install the Open Journal System version 3.X along with training for the editorial board. journal. This training aims to provide explanations and workshops on how to manage scientific journals to journal editors at Persada Bunda Pekanbaru college. There are 3 methods of community service; The first provides an explanation of the obligations of tertiary institutions and the role of each editor in managing electronic journals. Second, a workshop by directly testing the role of each user, and third, assistance for 1 year, from 2022 to 2023. Significant results can be seen from this community service. This can be seen from the management of the journal which is getting better and more advanced. At present the journal is well managed, so it can be concluded that this training was successful and the target of implementing the Open Journal System at Persada Bunda Pekanbaru College was achieved.